O Desenvolvimento do futsal paraibano sob olhar dos treinadores - Silva, Hugo Pablo da (2021)
Futsal is one of the most practiced sports in Brazil with different purposes, for leisure or competitive. This sport can be practiced by anyone, regardless of gender and age, resulting in benefits related to the health and well-being of practitioners. The aim of this study was to identify the purposes that help in the development of Futsal Paraibano. Methodological aspects: The research is descriptive and qualitative. The sample consisted of 21 Futsal coaches from the state of Paraíba, who work in teams that participate in the 5 main competitions in the territory of Paraíba. The variables investigated were age, education, time working with sport, branches of Futsal in which they work, category in which they work, competition in which they compete and purpose in the sport. Being measured by the questionnaire data collection instrument, consisting of closed and open questions. Data were analyzed qualitatively through descriptive statistics using absolute and relative frequency tables. Results: It was found that most coaches who compete in competitive Futsal in Paraíba are influenced by the following factors: Implement a new game method, Raise the level of sports teams and spread the sport in the state of Paraíba.